Addition of Ezetimibe to statins for patients at high cardiovascular risk: Systematic review of patient‐important outcomes. Issue 1 (16th January 2017) - Fei, Yutong; Guyatt, Gordon Henry; Alexander, Paul Elias; El Dib, Regina; Siemieniuk, Reed A.C.; Vandvik, Per Olav; Nunnally, Mark E.; Gomaa, Huda; Morgan, Rebecca L.; Agarwal, Arnav; Zhang, Ying; Bhatnagar, Neera; et al.
Abstract: Ezetimibe is widely used in combination with statins to reduce low‐density lipoprotein. We sought to examine the impact of ezetimibe when added to statins on patient‐important outcomes. Medline, EMBASE, CINAHL, and CENTRAL were searched through July, 2016. Randomized controlled trials (RCTs) of ezetimibe combined with statins versus statins alone that followed patients for at least 6 months and reported on at least one of all‐cause mortality, cardiovascular deaths, non‐fatal myocardial infarctions (MI), and non‐fatal strokes were included. Pairs of reviewers extracted study data and assessed risk of bias independently and in duplicate. Quality of evidence was assessed using the GRADE approach. We conducted a narrative review with complementary subgroup and sensitivity analyses. IMPROVE‐IT study enrolled 93% of all patients enrolled in the 8 included trials. Our analysis of the IMPROVE‐IT study results showed that in patients at high risk of cardiovascular events, ezetimibe added to statins was associated with i) a likely reduction in non‐fatal MI (17 fewer/1000 treated over 6 years, moderate certainty in evidence); ii) a possible reduction in non‐fatal stroke (6 fewer/1000 treated over 6 years, low certainty); iii) no impact on myopathy (moderate certainty); iv) potentially no impact on all‐cause mortality and cardiovascular death (both moderate certainty); and v) possibly no impact on cancer (low certainty). Addition of ezetimibe to moderate‐dose statins is likely to result in 17 fewer MIs and possibly 6 fewer strokes/1000 treated over 6 years but is unlikely to reduce all‐cause mortality or cardiovascular death. Patients who place a high value on a small absolute reduction in MI and are not adverse to use of an additional medication over a long duration may opt for ezetimibe in addition to statin therapy. Our analysis revealed no increased specific harms associated with addition of ezetimibe to statins.